The age dependence of T2 relaxation times of N‐acetyl aspartate, creatine and choline in the human brain at 3 and 4T. (11th January 2016) - Jiru, F.; Skoch, A.; Wagnerova, D.; Dezortova, M.; Viskova, J.; Profant, O.; Syka, J.; Hajek, M.
Abstract : Knowledge of the T 2 age dependence is of importance for MRS clinical studies involving subject groups with a wide age range. A number of studies have focused on the age dependence of T 2 values in the human brain, with rather conflicting results. The aim of this study was to analyze the age dependence of T 2 values of N‐acetyl aspartate (NAA), creatine (Cr) and choline (Cho) in the human brain using data acquired at 3T and 4T and to assess the influence of the macromolecule (MM) baseline handling on the obtained results. Two distinct groups of young and elderly controls have been measured at 3T ( T E = 30–540 ms, 9 young and 11 elderly subjects) and 4T ( T E = 10–180 ms, 18 young and 14 elderly subjects) using single‐voxel spectroscopy. In addition, MM spectra were measured from two subjects using the inversion‐recovery technique at 4T. All spectra were processed with LCModel using basis sets with different MM signals (measured or simulated) and also with MM signals included for a different T E range. Individual estimated T 2 values were statistically analyzed using the R programming language for the age dependence of T 2 values as well as the influence of the MM baseline handling. A significant decrease of T 2 values of NAA and Cr in elderly subjects compared with young subjects was confirmed. The same trend was observed for Cho. Significantly higher T 2 values calculated using the measured MM baseline for all studied metabolites at 4T were observed for both young and elderly subjects. To conclude, while the handling of MM and lipid signals may have a significant effect on estimated T 2 values, we confirmed the age dependence of T 2 values of NAA and Cr and the same trend for Cho in the human brain. Copyright © 2016 John Wiley & Sons, Ltd. Abstract : A significant decrease of T 2 values of NAA and Cr and the same trend for Cho in elderly subjects compared with young subjects was confirmed at both 3T and 4T. Spectra were processed with LCModel using basis sets with measured and simulated macromolecule signals. The difference between slope values of T 2 /age dependences for 3T and 4T were not significant. However, significantly higher T 2 values calculated using the measured MM baseline were observed for all studied metabolites at 4T.